The evolution of life size Barbie and Ken: Are they any closer to reality? - Sara Grafenauer; Belinda Durey; Kevin Norton (PLoS ONE, 2026)
Barbie and Ken dolls have been criticized over time for their overt misalignment of body shape in comparison with the average adult, and the possibility that this impacts the formative minds of children, particularly girls. Updating a previous examination of the original Barbie and Ken dolls from 1996, this study compared the body measures of the 2016 “Fashionista” range—including Curvy, Petite, Tall, and Standard Barbie models, and new Malibu Ken—with representative population data of young adult females and males using anthropometric techniques. A range of anthropometric girth measures plus height were taken from each doll, and body proportions were calculated. The rules of allometry were used to scale the dolls to a standardized adult height of 170.18 cm to determine the dimensions the dolls at this adjusted size. The dimensions were then compared to the same height-adjusted reference population norms used in the original study. The comparison revealed significant alterations in the dolls’ morphology compared with the original Barbie and Ken, with key measures of waist-to-hip and chest-to-waist ratios becoming more realistic and falling within the 95% confidence range of the population. According to z-score deviation data, Curvy Barbie fell closest to the mean for most of the scaled girth measures, while new Ken was closer to the mean for all girths except ankle. Design changes reflect a shift toward greater body diversity, with potential benefits for children’s health behaviours through the production of a broader range of more diverse, human-like dolls. Importantly, key measurements and body proportions were generally closer to the respective reference populations.